Genome-wide identification and characterization of circular RNAs for exogenous trehalose-mediated heat stress responses in tea plants (Camellia sinensis) - Zheng, Shizhong; Liu, Chufei; Zhou, Ziwei; Xu, Liyi; Ruan, Biyuan; Chen, Xiaohui (Frontiers in Plant Science, 2024)
Heat stress is one of the main environmental factors limiting the growth, yield and quality of tea plants (Camellia sinensis). Trehalose involved in plant responses to multiple adverse environmental stresses, including heat stress. However, the roles of circular RNAs (circRNAs) and their involvement in the trehalose response to heat stress remain unknown. In this study, we performed circRNA-sequencing to analyze the characteristics of circRNAs in trehalose-induced responses to heat stress in tea plants. A total of 11402 circRNAs were detected from CK, T (heat stress) and TT (heat stress + trehalose) samples. Among these circRNAs, 573, 620 and 550 circRNAs were identified as differentially expressed in the T vs. CK, TT vs. CK and TT vs. T comparison groups, respectively. Kyoto Encyclopedia of Genes and Genomes enrichment analysis was used to determine the potential function of circRNAs. The results suggested that host genes of differentially expressed circRNAs (DECs) were enriched in Non-homologous end-joining (NHEJ) and Homologous recombination (HR) pathways, implying a critical role of circRNAs in DNA double strand breaks (DSBs) repair. Moreover, the expression of DECs and their host genes related to NHEJ and HR were analyzed. The results showed that the expression level of circKu70-1 and circKu70-3 showed positive correlations with their host gene, ATP-dependent DNA helicase II 70 kDa subunit (CsKu70), while circKu70-2 exhibited an opposite expression trend. Similarly, circRad50 displayed a negative correlation with its host gene, DNA repair protein RAD50 (CsRad50). Notably, the expression of CsKu70 and CsRad50, which are crucial for initiating DSB repair, was decreased in the trehalose-treated (TT) samples. This finding suggests that trehalose may play a role in modulating the expression of circRNAs and their host genes involved in NHEJ and HR pathways, ultimately contributing to reduced DSB damage during heat stress. To